PERCEPTION ON HANDWRITING AMONG SECONDARY SCHOOL STUDENTS - Ashok, M. Leonard; Saumya (International Journal of Research -GRANTHAALAYAH, 2016)
Good handwriting serves as a primary tool of communication and knowledge assessment for students in classroom. Though computer and e- mail play an important role in our lives, nothing will ever replace the sincerity and individualism expressed through handwritten words. Our education system stress on student’s handwriting at primary level by introducing books like cursive writing, ruled notes and handwritten works. But as they upgrade, impact on handwriting slowly vanishes among students mainly at secondary level where they are stressed and deviated towards rote learning as a medium to fetch marks. But at this point we forget that only an aesthetic handwriting is a vehicle to impress and deliver our thoughts in the mind of evaluator, particularly when the evaluator is a stranger in case of public exams. This article is an attempt to find out the perception on handwriting among ninth standard school students and its influence on their academic achievement. This study has revealed that there is an impact of handwriting on academic achievement. Thereby it is stressed that handwriting should be given equal importance while teachers prepare their students for academic achievement.